"Stepping out of the ordinary": Exploring cross-cultural challenges of expatriates in the Kingdom of Saudi Arabia - Oscar Dousin; Rini Suryati Sulong (Rajagiri Management Journal (RAMJ), 2022)
Purpose - In the study of expatriation and expatriate adaptation, there are limited studies that focus on issues faced by expatriates working in foreign countries with very distinct cultures. This study aims to explore this idea through the experiences of western expatriates working in the Kingdom of Saudi Arabia (KSA). Two research questions were posed to examine the cross-cultural issues and challenges faced by expatriates in the KSA, as well as the role of cross-cultural training in expatriate adjustment. Design/methodology/approach - The study was guided by an interpretivism paradigm through a qualitative method by using a semi-structured in-depth interview approach. Interviews were conducted among 12 expatriates from the USA and UK who are currently working in KSA. Findings - A coding technique and theoretical thematic analysis was conducted to analyze the data. The results of this study highlighted three key themes that had a considerable influence on expatriates' adjustment, in particular: culture shock, lack of pre-departure training and the demand for an extensive cross-cultural training. Research limitations/implications - It is acknowledged that the existence of sub-cultures within the KSA would expose the respondents to varying cultural values within the community. Thus, future studies within a similar context should consider the influence of intra-cultural variations. Originality/value - The findings of the study emphasized on the importance understanding the cultural gap between home and host country and the individual cultural awareness of the expatriate. It calls attention to the need for a tailored and extensive pre-departure, cross-cultural training and a collaborative effort between employees' and managers to improve expatriates' motivation and retention.
Keywords: 650; Cross-cultural; Cultural awareness; Expatriate; Kingdom of Saudi Arabia (KSA); Training